2016
DOI: 10.1016/j.neuropharm.2015.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to opiates in female adolescents alters mu opiate receptor expression and increases the rewarding effects of morphine in future offspring

Abstract: Prescription opiate use and abuse has increased dramatically over the past two decades, including increased use in adolescent populations. Recently, it has been proposed that use during this critical period may affect future offspring even when use is discontinued prior to conception. Here, we utilize a rodent model to examine the effects of adolescent morphine exposure on the reward functioning of the offspring. Female Sprague Dawley rats were administered morphine for 10 days during early adolescence (post-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
32
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 77 publications
7
32
2
1
Order By: Relevance
“…Lower levels of morphine self-administration on a FR1 schedule is commonly interpreted as higher drug sensitivity (Arnold and Roberts, 1997; Carroll and Lac, 1997; Doherty et al, 2009; Koob et al, 1984). This is consistent with recent results using this same adolescent exposure regimen that showed increased place conditioning at low doses of morphine in a conditioned place preference paradigm (Vassoler et al, 2015). However, it could also be interpreted as a decrease in motivation to obtain morphine, which is more consistent with the PR, extinction, and reinstatement data.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Lower levels of morphine self-administration on a FR1 schedule is commonly interpreted as higher drug sensitivity (Arnold and Roberts, 1997; Carroll and Lac, 1997; Doherty et al, 2009; Koob et al, 1984). This is consistent with recent results using this same adolescent exposure regimen that showed increased place conditioning at low doses of morphine in a conditioned place preference paradigm (Vassoler et al, 2015). However, it could also be interpreted as a decrease in motivation to obtain morphine, which is more consistent with the PR, extinction, and reinstatement data.…”
Section: Discussionsupporting
confidence: 93%
“…The observed reduction in self-administration behaviors, however, should not necessarily be interpreted as a demonstration of a “protective effect” on offspring and grandoffspring with regard to addiction liability. Indeed, other data from our lab suggest additional behavioral and molecular modifications in these animals that would be expected to increase their vulnerability to addiction under various conditions (Byrnes, 2005a, b, 2008; Byrnes et al, 2011; Byrnes et al, 2013; Johnson et al, 2011; Vassoler et al, 2014b; Vassoler et al, 2015). Thus, what we suggest is that maternal exposure to morphine during adolescence alters the neurodevelopment of future offspring that impacts how they respond to drugs of abuse, which may be dependent upon a host of environmental and genetic factors.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…A growing body of evidence indicates that ancestral exposure to all of the major classes of abused drugs influences the physiology and behavior of descendants (Finegersh, Rompala, Martin, & Homanics, 2015;Finegersh, Ferguson et al, 2015;Szutorisz et al, 2014;Vassoler, White, Schmidt, Sadri-Vakili, & Pierce, 2013;Vassoler, Wright, & Byrnes, 2016;Vassoler et al, 2017;White, Vassoler, Schmidt, Pierce, & Wimmer, 2015;Yohn, Bartolomei, & Blendy, 2015). Several reports have consistently shown that sire exposure to cocaine influences cocaine-associated behaviors in the next generation.…”
Section: Introductionmentioning
confidence: 99%